Dampak Masuknya Turis Asing Terhadap Budaya Asli Masyarakat Sekitar Lokasi Pantai Lakey Desa Hu’u Kabupaten Dompu - Mintassrihardi Mintassrihardi; Selva Selva; Nurlaila Fitriyah (Universitas Muhammadiyah Mataram, 2018)
This study aims to describe the impact of foreign culture on the indigenous culture of the community around the Lakey beach location in terms of the positive and negative effects of foreign cultures around Lakey beach in Hu’u village, Dompu district. This study uses a type of qualitative data, the data in this study are in the form of words and actions obtained by observation, interviews and documentation. The main instrument in this study is data assisted by observation, documentation and interview guidelines. The research aids used are in the form of digital cameras and writing equipment. The validity of the data is obtained by triangulation techniques. The data analysis technique used is descriptive. Steps for analyzing data by reducing data, presenting data and drawing conclusions or verification. The results of this study show that 1) Westernized lifestyle tradition is one of them is a way of dressing that is not polite for women such as wearing pants or short skirts and clothes that cannot cover all bodies and some even wear a bikini (underwear only). They do not feel uncomfortable or ashamed of the opposite sex when they wear short clothing or do not cover their entire body. This is considered normal for them so they feel unafraid of the effects of short dressing. 2) Still adopting a consumptive lifestyle, some people still waste money just to do negative things like binge drinking when there are certain events, they are not reluctant to spend a lot of money just to get drunk. Not only to buy liquor they also often buy non-essential needs such as buying clothes that are quite expensive only to spend money. 3) The presence of foreign tourists also results in social inequality, in general, the people are picky about their associations, making the poor feel inferior to the more capable people. According to the Lakey beach community's response that some of the people who have capital or wealth are more likely to reduce associations with the less fortunate because they are considered less experienced in the business world. Until now there has also been no government intervention in responding to this. 4) But of the many negative impacts described by the Lakey community there is also a positive impact felt by the community, namely the creation of jobs and others. In this study many people complained of the impact of foreign cultures, so that people were worried about extinction of their own indigenous cultural values.